2019
DOI: 10.35453/nedjr-stmech-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymer Concrete at Ambient and Elevated Temperatures: Recent Developments and Challenges

Abstract: Geopolymer concrete (GPC) is attracting increasing attention due to its potential to replace ordinary Portland cement (OPC) concrete to reduce the carbon dioxide emissions from cement production. Although extensive research has been conducted in this area since the 1970s, its applications in engineering practice are still very limited. This paper briefly reviews the recent developments of GPC and its properties at ambient and elevated temperatures. It was found that GPC generally exhibits comparative propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…The influencing parameters which affect the fresh mechanical properties of GPC were determined as water to geopolymer solid ratio (W/GPS) and alkaline activator to binder ratio (Hardjito and Rangan 2005;Aliabdo et al 2016;Elyamany et al 2018). Tao and Pan (2019) concluded that the research efforts to make a flowable GPC are very scarce and the innovation of a superplasticizer for making cost effective GPC is also mandatory for practical application. In addition, self-compacting geopolymer concrete (SCGC) is a revolutionary concept in the construction industry to keep the people away from the compaction work on the material including highly concentrated alkaline liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The influencing parameters which affect the fresh mechanical properties of GPC were determined as water to geopolymer solid ratio (W/GPS) and alkaline activator to binder ratio (Hardjito and Rangan 2005;Aliabdo et al 2016;Elyamany et al 2018). Tao and Pan (2019) concluded that the research efforts to make a flowable GPC are very scarce and the innovation of a superplasticizer for making cost effective GPC is also mandatory for practical application. In addition, self-compacting geopolymer concrete (SCGC) is a revolutionary concept in the construction industry to keep the people away from the compaction work on the material including highly concentrated alkaline liquid.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with Provis, and van Deventer's [37,38] findings, which confirmed that the mechanism of geopolymerization could be strongly encouraged if the binder is treated at a temperature between 60 and 90 °C for 8-24 h. In addition, many researchers have already experienced a similar influence from curing temperatures, such as Bakria et al [29,38]. Therefore, curing at too extreme temperatures or for a significantly prolonged period may undermine the microstructure and cause increased shrinkage and fracturing, resulting in reduced strength [16,39].…”
Section: Influence Of Curing Temperature On Ucsmentioning
confidence: 77%
“…It was also observed that heat cured specimens resulted in more compressive strength than ambient cured specimens as polycondensation of geopolymer increases at elevated temperature due to complete dissolution of Al and Si, hence resulting in more hydrates products at early ages of curing and reduced the initial setting time [ 27 , 42 , 43 ]. As a matter of fact, it was also observed that the difference between compressive strengths were more at earlier ages as compared to later age of mixes [ 9 , [44] , [45] , [46] ]. Comparison of average compressive strengths of fly ash based GPC at various ages is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%